2012
DOI: 10.3310/hta16480
|View full text |Cite
|
Sign up to set email alerts
|

REMCARE: reminiscence groups for people with dementia and their family caregivers – effectiveness and cost-effectiveness pragmatic multicentre randomised trial

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
201
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(212 citation statements)
references
References 54 publications
7
201
4
Order By: Relevance
“…Unlike the other individual occupational therapy interventions, the only occupational therapy intervention in group (medium methodological quality) did not show any benefits for the dyads [95]. None of the investigated caregiver outcomes improved (primary outcome: general health of caregivers & secondary outcomes: distress, depression, relationship with the recipient, and anxiety).…”
Section: Group Based Occupational Therapy Interventionsmentioning
confidence: 99%
“…Unlike the other individual occupational therapy interventions, the only occupational therapy intervention in group (medium methodological quality) did not show any benefits for the dyads [95]. None of the investigated caregiver outcomes improved (primary outcome: general health of caregivers & secondary outcomes: distress, depression, relationship with the recipient, and anxiety).…”
Section: Group Based Occupational Therapy Interventionsmentioning
confidence: 99%
“…With regard to the results obtained on autobiographical memory after reminiscence intervention and life review procedure, results suggest that people with dementia who attend reminiscence sessions improve their autobiographical memory [85,99,100], being observed improvements in recalling both facts and events, that is, in semantic memory and episodic memory.…”
Section: Reminiscence Therapymentioning
confidence: 99%
“…Numerous studies [85,[101][102][103] have shown the benefits of this therapy, observing that elderly people with AD who had participated in a reminiscence program, compared to a control group that did not participate, showed an improvement in the amount of autobiographical memory, specifically semantic AM.…”
Section: Reminiscence Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Joint reminiscence has recently been evaluated in the REMCARE (REMiniscence groups for people with dementia and their family CAREgivers) trial 145 and did not identify any significant benefits for people with dementia or their carers. Indeed, there was evidence of increased anxiety for the family carers.…”
Section: Introductionmentioning
confidence: 99%